Validated RP-HPLC method for determining the levels of bromhexine HCl, chlorpheniramine maleate, dextromethorphan HBr and guaiphenesin in their pharmaceutical dosage forms. Issue 1 (1st January 2016) - Jain, Vishal; Sharma, Mukesh C.
Abstract: A simple, precise and accurate reverse phase high performance liquid chromatographic method was developed for the simultaneous estimation of bromhexine hydrochloride, chlorpheniramine maleate, dextromethorphan hydrobromide and guaiphenesin in their tablet dosage form. The chromatographic conditions were standardised using a Chromatopak C18 (25 cm × 4.6 mm i.d. × 5 μm) with UV detection at 265 nm, and the mobile phase consisted of methanol:acetonitrile:0.025 M phosphate buffer (50:25:25, v/v/v). The retention times of bromhexine hydrochloride, chlorpheniramine maleate, dextromethorphan hydrobromide and guaiphenesin were 16.254 min, 12.219 min, 6.156 min and 9.432 min, respectively. The calibration curves were linear with correlation coefficients of 0.9987, 0.9988, 0.9981 and 0.9981 over a concentration range of 4.0–24.0 μg/ml for bromhexine hydrochloride, 5.0–30.0 μg/ml for chlorpheniramine maleate, and 10.0–60.0 μg/ml for both dextromethorphan hydrobromide and guaiphenesin, respectively. The proposed method has been validated according to the ICH guidelines and was successfully applied to estimate the levels of four drugs in a combined formulation with good accuracy and precision.